2015
DOI: 10.1093/geronb/gbv100
|View full text |Cite
|
Sign up to set email alerts
|

Age Deficits in Facial Affect Recognition: The Influence of Dynamic Cues

Abstract: Together, these studies provide important and novel insights into the specific circumstances in which older adults may be expected to experience difficulties in perceiving facial emotions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 41 publications
8
68
1
2
Order By: Relevance
“…This might be explained by the fact that the healthy participants in our study, whose ages matched those of the individuals who had had brain injury, were significantly older than the participants in other studies, who were mostly recruited from the student bodies of universities and were, therefore, mostly in their 20s (12,15,16). As reported in previous studies, poorer performance at identifying emotional expressions is expected in older age (64,65). In addition, although the images used in our study were extracted from the same database used in other studies (12,15,16), and the images were randomly selected, the emotions shown in the images may have been more difficult to recognize than in the images used in other studies.…”
Section: Discussionmentioning
confidence: 55%
“…This might be explained by the fact that the healthy participants in our study, whose ages matched those of the individuals who had had brain injury, were significantly older than the participants in other studies, who were mostly recruited from the student bodies of universities and were, therefore, mostly in their 20s (12,15,16). As reported in previous studies, poorer performance at identifying emotional expressions is expected in older age (64,65). In addition, although the images used in our study were extracted from the same database used in other studies (12,15,16), and the images were randomly selected, the emotions shown in the images may have been more difficult to recognize than in the images used in other studies.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, it is not surprising that facial emotion recognition has been extensively investigated across the lifespan (Somerville et al, 2011), with particular focus on aging, which is frequently associated with isolation and social withdrawal. Results from previous studies are generally consistent, showing that older adults are less accurate than younger adults at discriminating and identifying negative facial expressions, especially those of “anger,” “fear,” and “sadness” (Calder et al, 2003; Ruffman et al, 2008; Chaby et al, 2015; Grainger et al, 2015; Templier et al, 2015; Mather, 2016). This emotional shift could emerge stepwise from the fourth decade of life (Calder et al, 2003; Chaby and Narme, 2009).…”
Section: Introductionmentioning
confidence: 61%
“…For example, some previous research found deficits in recognizing “sadness,” but not “fear” nor “anger” (e.g., Suzuki et al, 2007), whereas other studies found older adults' difficulties in recognizing “fear” and “anger,” but not “sadness” (e.g., Calder et al, 2003; Circelli et al, 2013). Finally, some studies found impairments for all the three emotions of “fear,” “anger,” and “sadness” (Wong et al, 2005; Grainger et al, 2015). The fact that older adults showed better expression identification for “joy” and “disgust” is consistent with other reports (Ruffman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala is specialized in the detection of facial expressions of fear [6,[7][8][9][10][11] whereas basal ganglia and insula are specialized in the detection of disgusted faces [3]. Several studies point out that older adults have more difficulty than younger when recognizing emotion from facial expressions, in particular for anger, sadness and fear [12,13]. Although there are many experimental studies that have focused on this aspect, the link between the impairment in other's emotions recognition and the cognitive modifications that occur during life span is still debated.…”
Section: Editorialmentioning
confidence: 99%